Influence of niobium and hafnium doping on the wear and corrosion resistance of coatings based on ZrN - Tao He; Zhylinski Valery; Alexey Vereschaka; Anthon Keshin; Yuanming Huo; Filipp Milovich; Catherine Sotova; Anton Seleznev (Journal of Materials Research and Technology, 2023)
The properties of coatings based on the ZrN system with the introduction of hafnium and zirconium (ZrN, (Zr,Nb)N and (Zr,Hf)N), deposited on a Ti6Al–4V titanium alloy substrate are compared. Coatings are deposited by controlled accelerated arc-physical vapor deposition, and the structure of the coatings is studied using a transmission electron microscope. A comparison is made of both the mechanical (hardness, wear resistance, scratch strength) and anticorrosion (in a 3 % solution of NaCl) properties. The (Zr,Hf)N coating (22 at% Hf and 78 at% Zr) has the maximum hardness (HV, 3225 ± 73) and wear resistance. This coating also exhibits higher corrosion resistance. In contrast, introducing Nb into the coating composition reduces the corrosion resistance. This combination of beneficial properties makes the (Zr,Hf)N coating useful for conditions in which the surfaces of parts must simultaneously have high wear resistance, strength, and corrosion resistance.